A Weaving Sword at Miletus? Combat or Weaving Sword and the Complexities of Gender Construction - Mazow, Laura B. (Archaeological Textiles Review, 2017)
A sword from a Mycenaean-style chamber tomb at Miletus in Turkey was described as being of the Hittite type, but it is dissimilar to traditional combat swords in having a tang at both ends. A sword with a tanged tip is ineffective as a weapon as the tip could easily break off. A better comparison is found in the weaving swords from Iron Age European contexts. When used as a weaving sword, the blade functions to beat in the warp. This paper considers the possibility that the Miletus sword is a weaving sword, reviews ethnographic, ethnohistoric and literary evidence for weaving swords in the ancient east Mediterranean world, and discusses the difficulty in recognising weaving swords in the archaeological record.